SOME OF RECOMMENDATIONS AND LEARNED LESSONS FROM BUILDINGS’ PERFORMANCE DURING THE RECENT TURKEY-SYRIA EARTHQUAKE - AL-AHMAR, RANIA; AL KOUSA, MAYADA AL AHMAD; WARDEH, GEORGE (Journal of Duhok University, 2023)
This paper reviews the performance of the buildings in Syria and Turkey during the February 6, 2023, Turkey-Syria earthquake. The damage and performance levels of buildings in the earthquake zones varied from minor or no damage to complete collapse. The damaged buildings are classified as seismic and non-seismic-designed buildings according to the earthquake codes. It has been found that there are many reasons for building collapses, such as non-consideration of seismic requirements in design or construction, poor quality of used materials, the possibility of exceeding the earthquake intensity than the design intensity level, insufficient foundations, and soil-related collapses. Based on the reasons mentioned above, general recommendations and future visions are highlighted to avoid the recurrence of such damages and collapses in future earthquakes.